Digital elevation models and delineation of antarctic glaciers using stereo capabilities of ASTER satellite images : steps on the way for a glacier monitoring on the Antarctic Peninsula - Jaña Obregón, Ricardo (2006)
Ongoing climate warming on the AP indicates that changes in the glacial system are occurring as a sensible reaction to the climatic variations. To study how develops this phenomenon the Antarctic Peninsula represents a source for cases study. To monitor changes in the variety of elements that compound the glacial system of the Antarctic Peninsula, a systematic analysis of an adequate inventory of glaciological features present in the region is required. The establishment of such an inventory is currently being coordinated and performed by the Department of Physical Geography of Freiburg University. Because of the vastness of the region and the logistic difficulties associated to the demanding sampling of field based glaciology activities, working approaches consisting in the extraction of glaciological parameters based on the use of remote sensing data are being used. However, a glacier inventory relies strongly on the geometry and geo-location of its features. The measuring of morphometric glacier parameters such as length, width, area, glacier front position, basin boundaries, and others morphometric measures where 3D coordinates are needed, requires a consistent spatial frame of reference. Only in this it case will be possible to compare variations in time in order to detect changes. Consequently, one of the big concern is the lack of geodetic and topographic data sets in the Antarctic Peninsula. Furthermore, both horizontal and vertical resolution of existent digital elevation models that cover the Antarctic Peninsula limit detailed terrain modelling at larger scales. Consequently, for glacier mapping at catchment scale there is a need to produce cartography and terrain elevation models that provide sufficient spatial resolution. This necessity is also required for geo-coding and geometrical correction of satellite data being used for the extraction of other glaciological parameters. Considering all this requirements and pursuing the idea that the use of satellite stereo imagery methods for topographic data ...